The Effect of Learning Strategy and Education Background on Student Learning Outcomes of Islamic Junior High Public School (MTsN 1) Simalungun - Erni Hanim Siregar; Rahmat Hidayat (BIRCU, 2019)
This research deals with The Effect of Learning Strategy and Education Background on Student Learning Outcomes of Islamic Junior High Public School (MTsN 1) Simalungun. One effort that can be done to improve learning outcomes is to improve the quality of learning by implementing better learning strategies.The method used in this study is a quasi-experimental method. The results show that there is an interaction between learning strategies with educational backgrounds, where students with an educational background in islamic elementary school (MI) are better taught using generative learning strategies compared to using expository learning strategies, while students with educational background in elementary school (SD) is better taught by using expository learning strategies compared to generative learning strategies. This is evidenced by the price of Fcount 35.48> Ftable 3.984.